LED 패키지 솔더 접합부의 기계적 신뢰성에 미치는 리플로우 횟수의 영향 - 이영철; Young Chul Lee; 윤정원; Jeong won Yoon; 정승부; Seung Boo Jung; 김광석; Kwang Seok Kim; 안지혁; Ji Hyuk Ahn; 고민관; Min Kwan Ko (대한금속·재료학회지, 48(11), 2010)
The research efforts on GaN-based light-emitting diodes (LEDs) keep increasing due to their significant impact on the illumination industry. Surface mount technology (SMT) is widely used to mount the LED packages for practical application. In surface mount soldering both the device body and leads are intentionally heated by a reflow process. We studied on the effects of multiple reflows on microstructural variation and joint strength of the solder joints between the LED package and the substrate. In this study, Pb-free Sn-3.0Ag-0.5Cu solder and a finished pad with organic solderability preservatives (OSP) were employed. A Cu6Sn5 intermetallic compound (IMC) layer was formed during the multiple reflows, and the thickness of the IMC layerincreased with an increasing number of reflows. The shear force decreased after three reflows. From the observation of the fracture surface after a shear test, partially brittle fractures were observed after five reflows.